Ptosoproctus gen. nov., a new genus with two new species of Shield-back Katydid, with the first record of genus Eulithoxenus Bey-Bienko, 1951 from China (Orthoptera: Tettigoniidae: Tettigoniinae: Drymadusini) - Shen, Zi-Hao; Yin, Zi-Xu; Lee, Michael; Liu, Yi-Jiao; He, Zhu-Qing; Wang, Zi-Fan; Wang, Tong-Xin (Zootaxa, 2021)
In this paper, one new genus, Ptosoproctus gen. nov., is established with two new species: P. lanzhouensis sp. nov. and P. baishishanicus sp. nov., described and illustrated based on material collected from northern China. The genus Eulithoxenus Bey-Bienko, 1951 is recorded from China for the first time. E. emeljanovi Mishchenko, 1968 is redescribed. Supplemental description of Uvarovina chinensis Ramme, 1939 is provided. COI and ND2 genes of the three Chinese Drymadusini genera mentioned above were used to reconstruct the phylogenetic tree. Molecular result support the validation of the new genus.